1976
DOI: 10.1161/01.res.39.2.204
|View full text |Cite
|
Sign up to set email alerts
|

Plasma catecholamines during paroxysmal neurogenic hypertension in quadriplegic man.

Abstract: Blood pressure, heart rate, and plasma catecholamine levels were measured in 16 quadriplegic subjects with physiologically complete cervical spinal cord transections above the level of the sympathetic outflow, and in 15 normal subjects (controls). In the quadriplegics the average resting blood pressure was 107/59 (mean, 75) mmHg, heart rate was 65 beats/min, and plasma norepinephrine (NE) and epinephrine (E) levels were 0.05 and 0.005 ng/ml, respectively. In the controls average resting blood pressure was 117/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
53
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(61 citation statements)
references
References 19 publications
8
53
0
Order By: Relevance
“…Peripheral noradrenaline supersensitivity has been documented in chronic human SCI (Mathias et al, 1976;Arnold et al, 1995), and there is additional evidence for more noradrenaline release per impulse (Gao et al, 2002) as well as an increased number of peripheral receptors post SCI (Velasco et al, 1997). In rats, approximately 50% of the AD pressor response can be attributed to vascular hyper-responsiveness (Collins and DiCarlo, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral noradrenaline supersensitivity has been documented in chronic human SCI (Mathias et al, 1976;Arnold et al, 1995), and there is additional evidence for more noradrenaline release per impulse (Gao et al, 2002) as well as an increased number of peripheral receptors post SCI (Velasco et al, 1997). In rats, approximately 50% of the AD pressor response can be attributed to vascular hyper-responsiveness (Collins and DiCarlo, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…27 Since CA has been implicated in the acute-exercise in duced elevations in T then one might expect an exaggerated T response in SCI athletes using boosting since T levels at rest are normal in this population. [18][19][20][21][22][23][24][25] In addition AD is associated with elevated cortisol (C) levels27 which have been suggested as a direct inhibitor of testosterone produc tion.28,29 The SCI athlete thus provides a model to examine the effects of CA and C on the exercise induced increment in testo sterone levels.…”
Section: Wheeler 1mentioning
confidence: 99%
“…Sensitive techniques for catecholamine measurement indicated that the hypertension during bladder contraction and muscle spasm is accompanied by a rise in levels of plasma noradrenaline but not plasma adrenaline (Fig. 2) (Mathias et al, 1976a). Noradrenaline is the neurotransmitter at sympathetic adrenergic nerve terminals, while adrenaline is the principal secretion from the adrenal medulla (Von-Euler, 1954).…”
mentioning
confidence: 99%